Visual symptoms with Sofosbuvir in hepatitis C treatment — a case report from Pakistan - Hasnain, Aliya; Shah, Sabeen; Hampejskova, Lindsay (Journal of the Pakistan Medical Association, 2023)
Hepatitis C virus infection is one of the main causes of chronic liver disease worldwide. The highly efficacious direct-acting antiviral (DAA) drugs licensed for therapy have revolutionised the treatment and are reported to have few side effects. Sofosbuvir is a pan-genotypic DAA that acts by inhibition of the hepatitis C NS5B polymerase. It has shown high efficacy in combination with several other drugs with low toxicity, a high resistance barrier, and minimal drug interactions with other hepatitis C DAA drugs. We describe a first of its kind case from Pakistan with visual disturbances caused by Sofosbuvir. A temporal relationship was observed between the treatment initiation and the onset of visual disturbances. The aim of this case report is to draw attention to the unanticipated side effects of this relatively new class of drug that have not been reported previously. Keywords: Sofosbuvir, Hepatitis C, Colour vision, Pakistan.